2022
DOI: 10.1186/s43045-022-00183-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between work–family conflict, sleep quality, and depressive symptoms among mental health nurses

Abstract: Background Nursing has a reputation for being one of the most stressful occupations. As a result of their work, many nurses suffer from anxiety and depression. Nurses are also at risk of poor sleep owing to their work nature. This study aimed to examine the relationship between work–family conflict, sleep quality, and depressive symptoms among mental health nurses. A descriptive cross-sectional study design was utilized in this study. Setting/sample: This study was conducted at El Azazi Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 55 publications
2
8
0
Order By: Relevance
“…Consistent with the findings of previous research [ 31 35 ], our study found that nurses experience more work-to-family conflict than family-to-work conflict, leading to a feeling of stress and guilt. This may be because work and family life are mutually incompatible to some extent.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the findings of previous research [ 31 35 ], our study found that nurses experience more work-to-family conflict than family-to-work conflict, leading to a feeling of stress and guilt. This may be because work and family life are mutually incompatible to some extent.…”
Section: Discussionsupporting
confidence: 92%
“…Not surprisingly, we found that workers with greater family demands (child and dependent care) and greater work demands (physical, psychosocial, temporal) had higher work–family conflict. Work–family conflict was positively associated with depression, as previously reported in studies of hospital nurses (Mohamed et al, 2022; Zhang, Duffy, & De Castillero, 2017) and in other occupational groups within the healthcare sector (Guille et al, 2017; Hao et al, 2015).…”
Section: Discussionsupporting
confidence: 80%
“…The above previous studies on the relationship between depression, sleep problems, and WFCs have frequently been conducted on nurses with high work stress or irregular working hours (Ding et al, 2020;Hwang & Yu, 2021;Mohamed et al, 2022;Zhang et al, 2017;Zurlo et al, 2020) The highlight of our study is that we were able to identify sleep problems as a mediator in the relationship between WFCs and depression in middle-aged females using data representing the Korean working environment. The Korean female labour force participation rate is closely related to a female's life cycle.…”
Section: Discussionmentioning
confidence: 87%
“…Although previous studies have evaluated the effects of WFCs on general workers (du Prel & Peter, 2015) and special occupational groups with high work stress such as nurses and truck drivers (Ding et al, 2020;Mohamed et al, 2022;Shin & Jeong, 2020;Zhang et al, 2017)…”
mentioning
confidence: 99%